Images of History through the Prism of National Consciousness - Gizatova, Gulnaz K.; Ivanova, Olga Gennadiyevna (Journal of History Culture and Art Research, 2017)
One’s people history is one of the most important sources that reproduce resources for the formation of ethnic subjectness. An appeal to history is accompanied by the formation of a certain image, both of a given ethnic community and of its historical development. Reconstruction of the experience of the previous development of an ethnos is accompanied by the construction of a special discourse in which the ethnic characteristics of this community, the system of its values, all the events of its historical past, often begin to be determined by subjective modality. The latter in its turn is determined by a variety of functions needed within the given discourse to construct this image. The image of history of people existing in the national consciousness, representing a unity of the objective and subjective, can also be viewed as a unity of continuity and, at the same time, development of the self-consciousness of the ethnos, since the past and history are the most important conditions for construction of the present and the future of the nation. The image of the history of a given nation existing in the national consciousness, representing a unity of the objective and subjective, can also be viewed as the unity of continuity and at the same time as the development of the self-consciousness of the ethnos, since the past and history are the most important conditions for the construction of the present and the future of the nation. Reproducing the national memory in the image of history, the ethnic community preserves the core of its culture, its spiritual wealth and at the same time creates internal sources of dynamics for its further development. At the same time, the image of history performs various functions in the structure of the national consciousness.